Salmonella typhi in the democratic republic of the congo: fluoroquinolone decreased susceptibility on the rise. - Octavie Lunguya; Veerle Lejon; Marie-France Phoba; Sophie Bertrand; Raymond Vanhoof; Jan Verhaegen; Anthony Marius Smith; Karen Helena Keddy; Jean-Jacques Muyembe-Tamfum; Jan Jacobs (PLoS Neglected Tropical Diseases, 2012)
Background Drug resistance of Salmonella enterica serovar Typhi (Salmonella Typhi) to first-line antibiotics is emerging in Central Africa. Although increased use of fluoroquinolones is associated with spread of resistance, Salmonella Typhi with decreased ciprofloxacin susceptibility (DCS) has rarely been reported in Central Africa. Methodology/principal findings As part of a microbiological surveillance study in the Democratic Republic of the Congo (DR Congo), Salmonella Typhi isolates from bloodstream infections were collected prospectively between 2007 and 2011. The genetic relationship of the Salmonella Typhi isolates was assessed by pulsed-field gel electrophoresis (PFGE). The antimicrobial resistance profile of the isolates was determined and mutations associated with DCS were studied. In total, 201 Salmonella Typhi isolates were collected. More than half of the Salmonella Typhi isolates originated from children and young adults aged 5-19. Thirty different PFGE profiles were identified, with 72% of the isolates showing a single profile. Multidrug resistance, DCS and azithromycin resistance were 30.3%, 15.4% and 1.0%, respectively. DCS was associated with point mutations in the gyrA gene at codons 83 and 87. Conclusions/significance Our study describes the first report of widespread multidrug resistance and DCS among Salmonella Typhi isolates from DR Congo. Our findings highlight the need for increased microbiological diagnosis and surveillance in DR Congo, being a prerequisite for rational use of antimicrobials and the development of standard treatment guidelines.